The unliganded long isoform of estrogen receptor beta stimulates brain ryanodine receptor single channel activity alongside with cytosolic Ca(2+) - Rybalchenko, Volodymyr (2009)
Ca(2+) release from intracellular stores mediated by endoplasmic reticulum membrane ryanodine receptors (RyR) plays a key role in activating and synchronizing downstream Ca(2+)-dependent mechanisms, in different cells varying from apoptosis to nuclear transcription and development of defensive responses. Recently discovered, atypical “non-genomic” effects mediated by estrogen receptors (ER) include rapid Ca(2+) release upon estrogen exposure in conditions implicitly suggesting involvement of RyRs. In the present study, we report various levels of co-localization between RyR type 2 (RyR2) and ER type β (ERβ) in the neuronal cell line HT-22, indicating a possible functional interaction. Electrophysiological analyses revealed a significant increase in single channel ionic currents generated by mouse brain RyRs after application of the soluble monomer of the long form ERβ (ERβ1). The effect was due to a strong increase in open probability of RyR higher open channel sublevels at cytosolic [Ca(2+)] concentrations of 100 nM, suggesting a synergistic action of ERβ1 and Ca(2+) in RyR activation, and a potential contribution to Ca(2+)-induced Ca(2+) release rather than to basal intracellular Ca(2+) concentration level at rest. This RyR/ERβ interaction has potential effects on cellular physiology, including roles of shorter ERβ isoforms and modulation of the RyR/ERβ complexes by exogenous estrogens.